KERJA SAMA INDONESIA-FILIPINA DALAM MEMPERTAHANKAN KONEKTIVITAS LAUT DI BAWAH KERANGKA BIMP-EAGA: Studi Kasus Rute Pelayaran Davao/General Santos-Bitung Periode 2019-2022 - Delvira Indah Sari Harahap (2023)
The Davao/General Santos-Bitung shipping route is one of the sea connectivity projects under the BIMP-EAGA subregional cooperation framework. This connectivity is believed to be able to reduce trade logistics costs and more broadly aims to develop the economy in the border areas of North Sulawesi (Indonesia) and Mindanao (Philippines). However, the operation of this shipping route stopped after the first voyage due to several obstacles and 2019 is a new chapter of efforts to re-operate the shipping route. This study uses the concept of subregional cooperation and connectivity with a descriptive qualitative research method to find a descriptive pattern regarding shipping route cooperation as a connectivity project under BIMP-EAGA. This analysis is based on the results of interviews and text interpretations (literature study). The research period began during a new round of efforts to re-operate shipping routes in 2019 and helped identify sustainability efforts carried out by Indonesia-Philippines until 2022. The results showed that this shipping route had not run optimally and had failed twice due to lack of service requests due to lack of commodities and tariffs that are not optimal. The technical obstacle is that this route takes the high seas which must use medium-large sized ships while commodities are still minimal. The Indonesian-Philippine government is committed to maintaining shipping routes by revitalizing shipping routes, accelerating infrastructure supporting shipping routes, and matching business between Indonesian-Philippine entrepreneurs. But in the end the shipping route could not run until the time this research was compiled. To ensure the sustainability of the shipping route, the Government of Indonesia-Philippines proposed to ADB as an advisor to carry out a more comprehensive follow-up study on the analysis of market demand and the feasibility of the Davao/GenSan-Bitung shipping route.